Proton pump inhibitors in patients treated with aspirin and clopidogrel after acute coronary syndrome - Gaspar, A; Ribeiro, S; Nabais, S; Rocha, S; Azevedo, P; Pereira, MA; Brandão, A; Salgado, A; Correia, A (Sociedade Portuguesa de Cardiologia, 2010)
INTRODUCTION: Clopidogrel is an antiplatelet agent converted to its active metabolite by cytochrome P-450 isoenzymes. Numerous drugs are known to inhibit P-450 isoenzymes, including proton pump inhibitors (PPIs), which are often associated with aspirin and clopidogrel to prevent adverse gastrointestinal effects. In vitro studies first showed that PPIs reduced the antiplatelet effect of clopidogrel, while recent clinical studies have raised concerns that the addition of a PPI to clopidogrel in acute coronary syndrome (ACS) patients could actually increase the risk of recurrent cardiovascular events. OBJECTIVE: The aim of this study was to evaluate whether the prescription of a PPI conferred a worse prognosis in patients discharged with aspirin and clopidogrel treatment after ACS. METHODS: A total of 876 patients admitted with ACS and discharged with aspirin and clopidogrel, with a planned duration of at least six months, from January 2004 to March 2008, were reviewed. Patients were classified in two groups according to whether or not a PPI was prescribed at discharge. The PPIs considered were those mainly metabolized by cytochrome P-450 2C19. We excluded patients with insufficient information available on either prescription or clinical records that could allow clearly confirm or exclude exposure to a PPI. Primary end points were six-month all-cause mortality and the composite of death, myocardial infarction and unstable angina at six months. RESULTS: Of the 802 patients considered for further analysis, 274 (34.2%) individuals were medicated with a PPI in addition to dual antiplatelet therapy. Patients taking PPIs were older, more often had renal insufficiency and less often had a history of coronary revascularization and smoking. They more often presented with Killip class >I and lower hemoglobin concentration on admission. There were no significant differences between the two groups in terms of medical treatment (during hospital stay and at discharge) or invasive procedures. By multivariate analysis, independent and positive predictors of PPI prescription were older age and lower hemoglobin concentration on admission. Patients taking PPIs had a slightly higher prevalence of six-month mortality (6.5% vs. 3.9%) and of the composite end point (12.9% vs. 9.2%), although without statistical significance. By multivariate analysis including potential confounding variables, the prescription of a PPI on top of aspirin and clopidogrel was still n ot associated with a worse prognosis. CONCLUSIONS: In the present study, PPI precription in addition to aspirin and clopidogrel after ACS was not associated with a worse six-month prognosis.
Keywords: Inibidores da Bomba de Protões; Síndrome Coronária Aguda; Aspirina; Clopidogrel